Low order multidisciplinary optimisation of counter-rotating open rotors - Smith, D.A.; Filippone, A.; Bojdo, N. (My University, 2018)
A recent renewed interest in CROR propulsion demands the need for suitable design and analysis tools. As an unconventional propulsion system, a multidisciplinary analysis should be made at the preliminary design stage in order to fully evaluate a designs suitability across a number of domains. To address this, this contribution presents a number of low order models ideally suited for the preliminary design stage. Low order models for the evaluation of aerodynamic, acoustic and structural performance are presented. Following this, a multi-objective optimisation is carried out. Suitable objective functions are presented to evaluate the performance over a number of flight phases. Using these, a number of designs are presented for take-off only, cruise only, and combined take-off and cruise. These designs are shown to be of greater performance with respect to a baseline design. The work presented highlights the potential of the low order models and optimisation routine as a preliminary design and analysis tool for CROR propulsion.